Gastroschisis and Omphalocele: A Case report - Shamima, Mosammat Nargis; Hossain, Mohd Alamgir; Jesmin, Shahela; Jahan, Nargis; Tasnim, Noshin (TAJ: Journal of Teachers Association, 2018)
Fetal gastroschisis and omphalocele are congenital defects of abdominal wall that are often diagnosed by prenatal ultrasound done for routine screening or for obstetric indications such as evaluating an elevated maternal serum alpha fetoprotein (AFP).Regular antenatal checkup and Prenatal ultrasound could potentially identify the overwhelming majority of abdominal wall defects and accurately distinguish omphalocele from gastroschisis. But in a developing country like Bangladesh neglected patients fail to seek antenatal visit and prenatal diagnosis. Here we report a case of gastroschisis and omphalocele diagnosed incidentally during last trimester. TAJ 2014; 27(2): 58-62